PENGARUH KONFLIK PERAN GANDA TERHADAP KINERJA WANITA KARIR DENGAN STRES KERJA SEBAGAI VARIABEL INTERVENING PADA PT. TELEKOMUNIKASI INDONESIA TBK - Eka Suhartini; Wahyuni Awalya Nahwi (AkMen JURNAL ILMIAH, 2019)
Problems with many women who occupy strategic positions at PT. Telekomunikasi Indonesia Tbk raises a problem that is unable to balance work and family so that multiple work family conflicts occur that cause job stress so that it can ultimately reduce performance. The purpose of this study was to determine the effect of multiple work family conflict and job stress on the performance of career women. The data analysis method used in this study is path analysis used to determine the direct and indirect effects. This research was conducted at PT. Telekomunikasi Indonesia Tbk by distributing questionnaires to 93 respondents. The sampling technique used is sensus sampling technique. The research hypothesis testing uses model test techniques (path analysis) with version 21 SPSS (Stastical Product and Service) application tools. The results of this study indicate that; Work-Family Conflict, Family-Work Conflict has a positive and significant effect on Job stress, and Job Stress has a positive and significant effect on performance, Work-Family Conflict and Family-Work Conflict with a positive and significant effect on Performance The implication of this research is that the company must show its seriousness in dealing with the problem of multiple work family conflict experienced by employees by holding periodic meetings between management and employees discussing various obstacles faced so far so that there is no conflict and job stress that can reduce employee performance